INTERACTIVE ENGLISH LITERACY ACTIVITIES FOR BEGINNER LEARNERS AT TK TEHILA IN REMOTE SOUTHWEST MALUKU - Dian Sartin Tiwery (J-Shelves of Indragiri (JSI), 2026)
This study investigated the implementation of interactive English literacy activities to support literacy and reading skill development among beginner learners at TK Tehila, Southwest Maluku, Indonesia. The study used a qualitative descriptive approach involving 20 kindergarten learners aged 4–6 years and 2 English teachers. Data were collected through classroom observation, interviews, documentation, field notes, and reflective discussions. The literacy activities implemented included storytelling, phonics instruction, songs, flashcards, games, and Total Physical Response (TPR). The findings revealed that learners became more active, confident, and enthusiastic during English literacy activities. Most learners showed improvement in vocabulary recognition, sound identification, listening comprehension, and reading readiness. Storytelling, songs, and movement-based activities increased learners’ participation because children connected language with pictures, gestures, and real-life experiences. In addition, the teachers improved their instructional competence and creativity in using interactive teaching strategies and locally available teaching media. The study concludes that interactive and child-centered literacy instruction effectively supports early English literacy development among beginner learners in remote educational settings. The findings also highlight the importance of teacher creativity, contextual learning, and sustainable literacy support programs in improving educational quality in remote areas.